Properties of self‐compacting concrete containing copper slag aggregate after heating up to 400°C. (6th April 2018) - Gong, Wei; Ueda, Takao
Abstract : In this paper, the influence of heating up to 400°C on properties of the self‐compacting concrete containing recycled copper slag fine aggregate was investigated. The residual mechanical properties such as compressive strength, splitting tensile strength, elastic modulus, and stress–strain curve of the heated concrete were measured with the change in the porosity of concrete. Moreover, the resistance against the penetration of chloride ions (Cl − ) into the concrete after the heating was also evaluated. For observing the micro‐structure around the fine aggregate in the concrete, scanning electron microscopy was employed. The experimental results showed that the compressive strength of the concrete decreased with the mixing of copper slag fine aggregate, although the residual compressive strength increased after heating up to 300°C with the rise in temperature. Mixing copper slag fine aggregate into concrete also reduced the residual elastic modulus and accelerated Cl − penetration into the self‐compacting concrete when the maximum temperature exceeded 200°C.